PEMBAHARUAN HUKUM PP NO 39 TAHUN 2021 TENTANG PENYELENGGARAAN BIDANG JAMINAN HALAL - Punira, Punira; Ratwati Gultom, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The implementation of the halal assurance sector is the process of regulating, supervising, and certifying products and services that meet halal standards. This abstract will explain the importance of implementing the halal assurance sector, including the role of certification bodies, the certification process, the challenges faced, and the benefits provided. The implementation of the halal guarantee package is very important in ensuring that the products and services consumed by Muslims are in accordance with the principles of the Islamic religion. This research aims to be able to find out what is related to the regulation of PP No. 39 of 2021 Concerning the Implementation of Halal Guarantees. This research uses normative qualitative research, namely the type of research that will be used, namely the study of literature by collecting reading sources and information that is relevant and related to the problem. The theory used is the theory of the legal system and legal certainty. The conclusion from this study is that there are rules regarding the offer of halal guarantee packages and the importance of providing halal guarantee packages.Keywords: Arrangement, Administration, Halal